Psychosocial and seizure factors related to depression and neurotic disorders among patients with chronic epilepsy in Nigeria (2004)
To establish the effect of psychosocial and seizure factors on Depression and Neurotic Disorders among clinically diagnosed Nigerian patients, with epilepsy. This study utilized the multivariate statistical design to evaluate the associations between some psychosocial and seizure factors on increase depression and neurotic disorders. The Neurology outpatient clinics of two tertiary facilities in Nigeria: Aro Neuro-psychiatric Hospital/World Health Organization Collaborating Centre, Abeokuta and the University College Hospital Ibadan, were used for the study. Two hundred and sixty four (264) consecutive clinic attendees with a clinical diagnosis of epilepsy participated in the study. Perceived Stigma Scale (PSS); Washington Psychosocial Seizure Inventory (WPSIModified): Becks Depression Inventory (BOI) and Crown-Crisp Experiential Index (CCEI). Significant main effect for seizure control, stigma, emotional adjustment, vocational adjustment, interpersonal adjustment, adjustment to seizures but not for age at onset of epilepsy, financial adjustment and gender, were recorded on depression. Similarly significant main effect for seizure control, stigma, emotional adjustment, adjustment to seizures but not for age at onset of epilepsy, gender, vocational adjustment, financial adjustment and interpersonal adjustment were recorded for neurotic disorders. The study highlights some of the factors, which may contribute to the understanding of epilepsy-related psychopathologies and implication for psychotherapeutic intervention among individuals with epilepsy in Nigeria.